Effects of over-expressing ethylene responsive transcription factor on expression of selected fruit ripening-related genes in oil palm (Elaeis guineensis Jacq.) mesocarp - Abd Hadi, Nur Annies; Abdullah, Siti Nor Akmar; Mohamad Azzeme, Azzreena; Al-Shanfari , Ahmed; Mohd Saud, Halimi (Universiti Putra Malaysia Press, 2015)
Gene expression is regulated mainly at the transcriptional level through binding of transcription factors to specific promoter regulatory elements. The expression profile of EgDREB, a transcription factor belonging to the AP2 family, was determined by reverse transcriptase (RT)-PCR and it was found that it was expressed at different stages of oil palm mesocarp development as well as in vegetative tissues (roots and leaves) but not in the mesocarp at the early ripening stage, which is 12 WAA (weeks after anthesis). Thus, the effects of over-expressing EgDREB on the transcriptional regulation of genes from five functional groups related to ripening were investigated in 12 WAA mesocarp of oil palm. Co-bombardment of 12 WAA mesocarp tissues with recombinant vector construct harbouring EgDREB and plasmid containing the GFP reporter gene was carried out. Fluorescent detection of GFP and verification via RT-PCR using GFP-specific primers enabled selection of successfully transformed tissues. Using transient expression assay, it was demonstrated that over-expression of EgDREB results in up-regulation of translationally controlled tumor protein (TCTP) and type 2 metallothionein-like genes (MET2a and MET2b). These proteins are categorised under biogenesis of the cellular component and proteins with binding functions or cofactor requirements. More specifically, the roles of metallothioneins are in homeostasis of essential metal ions and oxidative stress response. This may suggest that EgDREB is involved in regulating cellular processes related to the roles of these three proteins.